2002
DOI: 10.1093/ajcn/75.3.519
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of energy expenditure estimates from doubly labeled water, a physical activity questionnaire, and physical activity records

Abstract: Background: Various methods are used by epidemiologists to estimate the energy cost of physical activity; these include physical activity records and recalls. However, there is limited validation of these methods against the doubly labeled water technique for determining energy expenditure (EE). Objective: We compared EE as estimated by indirect methods (physical activity records and recall questionnaires) used in epidemiologic studies with EE obtained from doubly labeled water (EE DLW ) in free-living men. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
91
3
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(103 citation statements)
references
References 22 publications
6
91
3
2
Order By: Relevance
“…Activity diaries in the general population have been shown to overestimate physical activity (Conway et al, 2002). In pregnant women, activity diaries were shown to overestimate physical activity by around 400 kcal/day, whereas accelerometry underestimated activity by a similar amount compared with heart rate telemetry (Stein et al, 2003).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Activity diaries in the general population have been shown to overestimate physical activity (Conway et al, 2002). In pregnant women, activity diaries were shown to overestimate physical activity by around 400 kcal/day, whereas accelerometry underestimated activity by a similar amount compared with heart rate telemetry (Stein et al, 2003).…”
Section: Discussionmentioning
confidence: 95%
“…The difficulties involved in taking such measurements are well established (Avons et al, 1988). Conventional techniques used within the general population include pedometry, accelerometry, heart rate monitoring and activity records obtained through diaries or recall (Westerkerp, 1999;Conway et al, 2002). Although doubly labelled water is now the gold standard for the assessment of energy expenditure, the costs associated with this method restrict its use in population studies (Goldberg et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…More detailed questionnaires intend to assess duration, frequency, and intensity of activites accurately, but because of their complexity, they may also result in a lower compliance and lower validity. [5][6][7][8] Less detailed questionnaires are easy to use, but are often less accurate and do not assess different dimensions of physical activity such as duration, frequency, and intensity. 3,9 As a result, different approaches have been developed to assess either habitual or actual physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…5 Such a record requires a high compliance and encouragement of the test persons to list all activity changes. Moreover, test persons may alter their usual activity habits when the recall is carried out for a longer time period.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, our analyses revealed that the age-related deviations in REE were independent from both the overall level of activity as well as the number of periods of vigorous physical activity. However, it is important to indicate that although a physical activity diary has limitations including the ability of subjects to adequately perceive exercise intensity (Conway et al, 2002), these findings likely have public health relevance. Indeed, they suggest that maintaining physical activity levels comparable to those of younger individuals may be insufficient to prevent an age-related increase in adiposity.…”
Section: Variablesmentioning
confidence: 99%